Karakteristik Biometrik, Morfologi Telur, dan Habitat Ikan Padi Oryzias javanicus (Beloniformes, Adrianichthyidae) Asal Desa Linduk, Pesisir Teluk Banten - Herjayanto, Muh.; Syamsunarno, Mas Bayu; Syarif, Ahmad Fahrul; Solahudin, Edo Ahmad; Rahmayanti, Novita; Rizki, Exel Muhamad; Paricahya, Akhsan Fikrillah; Ahmadi, Kamaludin; Gani, Abdul; Widiyawan, Esa Rama; et al. (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Information on the biometric characteristics, egg morphology, and habitat of O. javanicus are very important for its use as model fish in the laboratory, ornamental fish, and environmental bioindicators. Therefore, research is needed to analyze the biometric character, egg morphology, and habitat of ricefish O. javanicus in the brackish water pond of Banten Bay. This research was conducted non-eperimentally by observing biometric characters to examine meristic, morphometric, and sex dimorphism characteristics. Observations of egg morphology were macroscopic and microscopic characteristics. Habitat characteristics were observed by measuring water quality in situ. The results showed that O. javanicus from Linduk had meristic characteristics D.6–7; A.21–22; P.9-10; V.5–6 and sex dimorphism in the shape and size of the dorsal and anal fins. Blue metallic color pattern on the head and yellow color on the fins are potentially ornamental fish. O. javanicus eggs have a diameter of 1.08 ± 0.02 mm, are equipped with attaching filaments and non-attaching. The non-attaching filaments are 0.14 ± 0.03 mm in length. The percentage of yolk area was 73.7 ± 4.85%, and the oil droplet area was 8.3 ± 0.54% of O. javanicus at the gastrula stage with egg yolk volume 0.349 ± 0.048 mm3. Water quality in this study is a reference for rearing O. javanicus in the laboratory.